Review on Economic valuation of solid waste management in Bandar Lampung, Lampung - Iing Lukman; Diah Ayu Wulandari Sulistyaningrum; Taqwan Thamrin (Bandar Lampung University (UBL), 2014)
The characteristics of solid waste in Bandar Lampung have not been identified yet. Then the management of solid waste is still looking for the best model and its policy. The contribution from women in the municipal solid waste management has not been adequate mainly due to its policy which has not been suitable for women. Therefore, the women have not had bargaining position in the environmental management. The research project will contribute to the household solid waste management, which directly involving mothers or women to have a role in the determining what products should be used in the daily business which environmentally friendly.